2019
DOI: 10.1038/s41598-019-39699-w
|View full text |Cite
|
Sign up to set email alerts
|

New ecosystems in the deep subsurface follow the flow of water driven by geological activity

Abstract: Eukarya have been discovered in the deep subsurface at several locations in South Africa, but how organisms reach the subsurface remains unknown. We studied river-subsurface fissure water systems and identified Eukarya from a river that are genetically identical for 18S rDNA. To further confirm that these are identical species one metazoan species recovered from the overlying river interbred successfully with specimen recovered from an underlying mine at −1.4 km. In situ seismic simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Deep biosphere microbial communities reside either as planktic communities in deep groundwater or sessile communities on surfaces [ 7 , 8 , 9 ]. The formation of biofilms and microcolonies on fracture zone rock surfaces has been demonstrated in various deep subsurface settings, e.g., gold mines and deep subseafloor crust [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Drake et al (2017, 2018) recently revealed fossil fungal cryptoendolithic communities with hyphae-like structures from deep drill core rock surfaces, thus linking fungi to deep subsurface biofilms [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep biosphere microbial communities reside either as planktic communities in deep groundwater or sessile communities on surfaces [ 7 , 8 , 9 ]. The formation of biofilms and microcolonies on fracture zone rock surfaces has been demonstrated in various deep subsurface settings, e.g., gold mines and deep subseafloor crust [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Drake et al (2017, 2018) recently revealed fossil fungal cryptoendolithic communities with hyphae-like structures from deep drill core rock surfaces, thus linking fungi to deep subsurface biofilms [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…H. mephisto separated from Caenorhabditis at least 22 million years ago 52,64 , and likely over 100 million years ago 65 , though calibrating the nematode molecular clock is difficult because of their poor fossil record 64 . Our data suggest that nematodes access the deep subsurface from surface waters facilitated by seismic activity 66 . This ransition from surface to deep subsurface would be expected to exert strong selective pressures on their genomes, which in nematodes are particularly evolutionarily dynamic 6,7,1012 .…”
Section: Discussionmentioning
confidence: 72%
“…H. mephisto separated from Caenorhabditis at least 22 million years ago 52,64 , and likely over 100 million years ago 65 , though calibrating the nematode molecular clock is difficult because of their poor fossil record 64 . Our data suggest that nematodes access the deep subsurface from surface waters facilitated by seismic activity 66 . This transition from surface to deep subsurface would be expected to exert strong selective pressures on their genomes, which in nematodes are particularly evolutionarily dynamic 6,7,10-12 .…”
Section: Discussionmentioning
confidence: 72%